Concomitant diagnosis of sexually transmitted infections and human monkeypox in patients attending a sexual health clinic in Milan, Italy. Issue 1 (28th November 2022) - Rizzo, Alberto; Pozza, Giacomo; Salari, Federica; Giacomelli, Andrea; Mileto, Davide; Cossu, Maria Vittoria; Mancon, Alessandro; Gagliardi, Gloria; Micol, Bianchi; Micheli, Valeria; Capetti, Amedeo; Antinori, Spinello; et al.
Abstract: In 2022, many monkeypox (MPX) outbreaks have been documented in countries where MPX was not endemic. It spread all around the world, especially in European Union and United States. While MPX is classically considered to be transmitted through close contact with lesions, the hypothesis of sexual transmission has been proposed. This study considered a total of 49 patients suspected for MPX that were also tested for other sexually transmitted infections (STIs), including Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium, and Trichomonas vaginalis . The data from coinfected patients suggested that MPXV and STIs might share the same route of inoculum, corroborating the hypothesis of possible sexual transmission for the emerging poxvirus. And like any other STI, MPX should be considered without stigmatization.